DEVELOPMENT OF INTELLECTUAL POSSIBILITIES ON THE BASIS OF PEDAGOGICAL SUPPORT OF PRESCHOOL EDUCATIONAL STUDENTS. (Conference Zone, 2021)
This article is about the development of intellectual abilities of preschoolers on the basis of pedagogical support.